Lineament Patterns and Structural, Tectonic, and Neotectonic Control in the Relief of the Pancas Region (Espírito Santo, Southeast Brazil) - Luna da Silva, Marcos Cesar; Bricalli, Luiza Leonardi (Sociedade & Natureza, 2023)
The main objective of this research is to investigate the lithostructural, tectonic, and neotectonic control on the relief of the Pancas region (Espírito Santo, Southeastern Brazil). The methodology was organized into computer and field analyses. In a computer, lineament and structural trend maps were generated from the manual extraction technique using editing tools of ArcGIS 10.3.1™ software (ESRI, 2012) over a Digital Elevation Model (DEM) with different artificial illumination (scale 1:110.000) and orientation rosettes were generated. The geological and geomorphological maps were organized/elaborated with ArcGIS from the Geographic Information System (GIS). The cartographic bases were configured in the UTM projection system, and DATUM SIRGAS 2000, zone 24S, and later analyzed and compared with the data of the orientations of the dedicated lineaments, with the orientation of the studied outcrop failures and with the existing literature. The results presented NW-SE/NNW-SSE and NE-SW/NNE-SSW orientations, with the predominance of NNW-SSE and NW-SE orientations identified in the analysis of the lineaments and structural trends, similar to the orientations of the geological faults and neotectonic faults present in the studied area, reflecting the regional structuring of the area, presenting the same orientations as the Colatina Belt. The secondary orientations of the Araçuaí Orogen (NE-SW), the identification of morphotectonic features, the presence of abrupt topographic differences (topographic profiles), and the identification of tectonic regions (base surface map) and tectonic blocks (scanning profile) demonstrate the tectonic control in the relief of the Pancas-ES region, achieving the objective of this research.